The N6-Methylandenosine-Related Gene BIRC5 as a Prognostic Biomarker Correlated With Cell Migration and Immune Cell Infiltrates in Low Grade Glioma - Jiang, Xiulin; Shi, Yulin; Chen, Xi; Xu, Haitao; Huang, Xiaobin; Li, Lihua; Pu, Jun (Frontiers in Molecular Biosciences, 2022)
Abstract Glioma is the most common malignant brain tumor in human adults, with a low 5-year overall survival (OS) rate (35%). Emerging evidence has demonstrated that BIRC5 plays a critical role in the regulating the cell apoptosis and diverse cancer progression. Whereas, there was no study focused on the immunological function and upstream regulation mechanism of BIRC5 in the progression of LGG. In this study, BIRC5 expression and it’s clinical characteristics of glioma patients were evaluated by using CGGA, TCGA, GEO, Rembrandt and Gravendeel database. We using the Kaplan-Meier and the receiver operating characteristic (ROC) curve analysis the potential prognosis of BIRC5 in LGG. KEGG and GO enrichment were examinedthe function roles of BIRC5. TIMER and TISIDB databases employed to examine n between the BIRC5 expression and immune cell infiltration in LGG. GDSC and CTRP databases used to examine the potential drugs that target the BIRC5. We using transwell and wound healing assays to determine the biology functions of BIRC5 on the cell migration ability of glioma cells. Our results demonstrated that BIRC5 was highly expression in LGG and correlated with tumor grade, poor prognosis and it’s diverse clinical characteristics, including the histology subtypes, IDH1 mutation, 1p/19q chromosomal co-deletion, chemotherapy status and MGMT promoter methylation status. GO and KEGG analysis shown that BIRC5 mainly involve in the cell proliferation and immune response related signaling pathway. We also found that BIRC5 was significantly correlated with m6A regulator and diverse drugs sensitivity. TIMER and TISIDB database suggested that BIRC5 was associated with the diverse immune cell infiltration and immune modulator in LGG. Collectively, these results demonstrated that BIRC5 may be a potential prognostic biomarker and is correlated with cell migration and immune infiltration in LGG.